Prawn Fishery in Gujarat Location of New Prawn Grounds Off Veraval - Gujarat, Survey; Research Division Department of Fisheries (Fishery Technology, 1965)
Prawn Fishery in Gujarat Location of New Prawn Grounds Off Veraval